Long-term medical and productivity costs of severe trauma: Results from a prospective cohort study - van der Vlegel, Marjolein; Haagsma, Juanita A.; Havermans, Roos J. M.; de Munter, Leonie; de Jongh, Mariska A. C.; Polinder, Suzanne (PloS one, 2021)
Through improvements in trauma care there has been a decline in injury mortality, as more people survive severe trauma. Patients who survive severe trauma are at risk of long-term disabilities which may place a high economic burden on society. The purpose of this study was to estimate the health care and productivity costs of severe trauma patients up to 24 months after sustaining the injury. Furthermore, we investigated the impact of injury severity level on health care utilization and costs and determined predictors for health care and productivity costs. This prospective cohort study included adult trauma patients with severe injury (ISS[greater than or equal to]16). Data on in-hospital health care use, 24-month post-hospital health care use and productivity loss were obtained from hospital registry data and collected with the iMTA Medical Consumption and Productivity Cost Questionnaire. The questionnaires were completed 1 week and 1, 3, 6, 12 and 24 months after injury. Log-linked gamma generalized linear models were used to investigate the drivers of health care and productivity costs. In total, 174 severe injury patients were included in this study. The median age of participants was 55 years and the majority were male (66.1%). The mean hospital stay was 14.2 (SD = 13.5) days. Patients with paid employment returned to work 21 weeks after injury. In total, the mean costs per patient were [euro]24,760 with in-hospital costs of [euro]11,930, post-hospital costs of [euro]7,770 and productivity costs of [euro]8,800. Having an ISS [greater than or equal to]25 and lower health status were predictors of high health care costs and male sex was associated with higher productivity costs. Both health care and productivity costs increased with injury severity, although large differences were observed between patients. It is important for decision-makers to consider not only in-hospital health care utilization but also the long-term consequences and associated costs related to rehabilitation and productivity loss.